PENGARUH DISIPLIN DAN MOTIVASI TERHADAP INDEKS PRESTASI MAHASISWA PRODI AKUNTANSI UNIVERSITAS NUSA PUTRA - Rukoyah, Siti (Nusa Putra University, 2020)
This type of research is quantitative. The population of this study was 100 students of the Accounting Study Program. The research sample used a random sampling method, and part of the population selected was 33 people. Multiple linear regression is a data analysis technique used in this study, using partial and simultaneous hypothesis testing and using the coefficient of determination. The prerequisite analysis test was the normality test which was carried out using the Kolmogorov Smirnov test, then the multicollinearity test, then the heteroscedasticity test and then the linearity test before carrying out the test analysis. The results obtained from this study indicate that discipline and motivation have an effect on the Student Achievement Index.